El usuario de bibliotecas ante los nuevos soportes y los nuevos servicios: el usuario electrónico - Gimeno Perelló, Javier (Revista General de Información y Documentación, 2006)
The transformation of the traditional supports forms of information in electronic, digital and telematic documents has supposed a cultural revolution only comparable to irruption of the printing like key indication of the modernity. The NTIC has not only generated new documental forms, but also, new services of information whose incidence in the users is not still sufficiently studied. We intend an open reflection about the impact that the work of the documental centers, by means of the new supports and technological services, they exercise on the users of the information.
Keywords: Information users; Information and Communication Technologies; Documentaries supports; Information services; Technological Revolution